Immune imprinting and antibody profiles to SARS-CoV-2 in urban and rural Ghana - Martin Montiel-Ruiz; Elvis S. Lomotey; Elizabeth Obeng-Aboagye; Isaac Quaye; Daniel A. Odumang; Florence B. Amakye; Bernard A. Logonia; Salomé Lochmann; Joseph A. Hayford; Dickson K. Osabutey; Angelica Daakyire; Christopher Dorcoo; et al. (iScience)
Summary: Infections with SARS-CoV-2 and the development of immunity to the virus and its antigenic variants have been unevenly documented globally, with African populations particularly understudied. As SARS-CoV-2 transitions toward being an endemic pathogen, a more nuanced understanding of immune protection in diverse populations is required. In 2023, we conducted a cross-sectional study of 1,000 Ghanaian residents to assess SARS-CoV-2 prevalence and antibody correlates of immunity against SARS-CoV-2 variants. We found an active SARS-CoV-2 infection rate of 1.3% and a 57% vaccination rate. We observed anti-SARS-CoV-2 Spike plasma antibody sero-positivity of 98.7%, with urban compared to rural residents having higher anti-SARS-CoV-2 plasma and saliva antibody concentrations. Vaccinated and urban individuals exhibited significantly greater Spike-pseudotyped virus neutralization than nonvaccinated and rural individuals. Notably, plasma antibodies preferentially bound Wuhan-Hu-1 over Omicron Spike variants. Our findings indicate significant prior and ongoing SARS-CoV-2 transmission as well as immunological imprinting by Wuhan-Hu-1-like SARS-CoV-2 in Ghana.